Multiple and interpersonal trauma are risk factors for both post‐traumatic stress disorder and borderline personality disorder: A systematic review on the traumatic backgrounds and clinical characteristics of comorbid post‐traumatic stress disorder/borderline personality disorder groups versus single‐disorder groups. (24th August 2019) - Jowett, Sally; Karatzias, Thanos; Albert, Idit
Abstract : Background: Both borderline personality disorder (BPD) and post‐traumatic stress disorder (PTSD) are associated with exposure to traumatic events and are highly comorbid. No review to date has addressed the clinical presentations and traumatic backgrounds associated with these disorders although this work is essential for the development of effective interventions. Objectives: To systematically explore similarities and differences in traumatic history and clinical presentation in comorbid BPD and PTSD as compared to PTSD or BPD alone. Method: The Web of Science, Cochrane Library, PsycINFO, MEDLINE, and PILOTS databases were searched systematically. Eligible studies included adult populations, compared comorbid BPD/PTSD to a single disorder, and published in English. Results: A total of 10, 147 cases across 33 studies were included: 2, 057 comorbid BPD/PTSD, 2, 648 BPD only, and 5, 442 PTSD only. The comorbid group overall reported greater exposure to multiple and interpersonal trauma and elevated emotion dysregulation compared to both single‐disorder groups. In terms of methodological quality, most papers achieved a Fair rating with improvements required in minimizing bias through recruiting adequate and representative samples, and reporting on traumatic exposure. Conclusion: Multiple and interpersonal trauma might have a unique role in the development of comorbid BPD/PTSD features, particularly so for emotion dysregulation. Future research is required to unravel the unique characteristics of interpersonal trauma that can generate BPD and PTSD symptoms. Practitioner points: Practitioners should routinely assess for interpersonal trauma considering its impact. Tackling emotion regulation difficulties might promote recovery from both PTSD and BPD symptoms. Presence of self ‐injury might be used to discriminate between PTSD and BPD and offer suitable interventions.